War for peace in Pakistan - Ali, Syed Masroor (International Educative Research Foundation and Publisher (IERFP), 2013)
Pakistan because of its geographical location became a front line state in the war against terror since the attack on the World Trade Centre on September 11, 2001. Pakistan decided to align with USA to combat the fundamentalist. It’s a war whose main purpose is to save people from terrorism but now lives of Pakistan own citizens are at stake. Innocent citizens have become the targets of deadly attacks. It has resulted in much more loss of lives than 9/11 attack. One obvious and tragic price of this open war is the toll of death and destruction. But there is an additional cost, a psychological cost borne by the survivors of war. The civilian population, and the children who have lost their parents in this war are the real casualties we need to take into consideration. This article will highlight the psycho-social aspects of war which could not achieve peace yet.